2005
DOI: 10.1002/j.1556-6978.2005.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

First-Semester Experiences of Counselor Education Doctoral Students

Abstract: This qualitative study explored 4 counselor education doctoral students' 1st-semester experience. Data analysis revealed students experienced vicissitudes of thought and emotion that varied from self-doubt to beliefs in their abilities, received information and made decisions about how to engage in their responsibilities, and felt affirmation of their capabilities and qualifications. With this affirmation, students were able to make decisions about further experiences they would have during their program. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Examples of instrument questions include "I understand theories and skills of leadership," I believe I can demonstrate the ability to provide leadership or contribute to the leadership efforts of professional organizations and/or counseling programs," and "I believe I can demonstrate the ability to advocate for the profession and its clientele." In addition, a review of the counselor education leadership development literature revealed 14 leadership development experiences (Hughes & Kleist, 2005;Magnuson, Wilcoxon, & Norem, 2003;Nelson, Oliver, & Capps, 2006;Niles, Akos, & Culter, 2001;Protivnak & Foss, 2009;Rabinowitz, 1997). Participants were asked to indicate which, if any, of the following 14 experiences were the most important influences in the development of their leadership skills and abilities:…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of instrument questions include "I understand theories and skills of leadership," I believe I can demonstrate the ability to provide leadership or contribute to the leadership efforts of professional organizations and/or counseling programs," and "I believe I can demonstrate the ability to advocate for the profession and its clientele." In addition, a review of the counselor education leadership development literature revealed 14 leadership development experiences (Hughes & Kleist, 2005;Magnuson, Wilcoxon, & Norem, 2003;Nelson, Oliver, & Capps, 2006;Niles, Akos, & Culter, 2001;Protivnak & Foss, 2009;Rabinowitz, 1997). Participants were asked to indicate which, if any, of the following 14 experiences were the most important influences in the development of their leadership skills and abilities:…”
Section: Instrumentationmentioning
confidence: 99%
“…The range of potential responsibilities involved with managing an organization include writing policies, setting goals, setting and accomplishing a mission, organizational culture, enforcing organizational norms, overseeing budget and monetary matters, setting priorities, resolving conflicts with outside agencies, setting training requirements, ensuring mission accomplishment, and managing compensation (Maister, 2001). Hughes and Kleist (2005) observed that despite counselor education's emphasis on leadership, the field has placed little emphasis on studying doctoral students' leadership training experience. One study (Zimpfer, Cox, West, Bubenzer, & Brooks, 1997) consisted of a survey of the leadership development aspects of counselor education programs.…”
Section: Introductionmentioning
confidence: 95%
“…This involvement can help students to acclimate to their first year of doctoral studies (Hughes & Kleist, 2005), and it may create an environment in which students feel that their voices are being heard and their goals are valued. Further, when provided a forum to verbalize motivations, students may better articulate needs.…”
Section: Implications For Cesmentioning
confidence: 99%
“…Protivnak and Foss (2009) also determined that departmental culture influenced CES doctoral students' successful completion of their program and cited examples of collaborative environments where faculty invited students to teach or write, were responsive to students' needs, and generally made students feel included. These activities can be useful for increasing student involvement and gaining a sense of purpose within their program, which are helpful factors in finding self-assuredness and belonging for first-semester doctoral students (Hughes & Kleist, 2005).Although previous studies provided information about student motivations in general, due to the various preparatory experiences and career paths afforded by the CES degree and the implications for academic match and mentorship, a greater understanding of the motivations of CES students is warranted. Thus, the current study sought to inform the question, "What motivates students to pursue a doctorate in CES?…”
mentioning
confidence: 99%
See 1 more Smart Citation